PENGARUH MANAJEMEN PEMBELAJARAN AQIDAH AKHLAK TERHADAP MOTIVASI BELAJAR SISWA KELAS XI-MIPA DI MAN 2 MOJOKERTO - Tetik Erna Wati; Andika Hariyanto Surbakti (TA'LIM : Jurnal Studi Pendidikan Islam, 2023)
Learning management is a directed and measurable process for the realization of learning objectives. In connection with learning management, there are several components that are used as benchmarks for assessment and evaluation in the learning that has been done. The indicators used include; learning planning, learning implementation and assessment. If each function is carried out optimally and in line with a predetermined plan, then the learning process can be achieved properly. This study examines the effect of applying Aqidah Akhlak learning management on students' learning motivation. The approach in this study uses quantitative methods, namely data collected in the form of numbers through interviews and questionnaires. The subjects of this study were students of class XI MIPA MAN 2 Mojokerto. This research was carried out pretest and post-test with the results tested using the paired T test with the calculation results of each variable, the motivation variable was 6.860 and the learning achievement variable was 6.384. The results were more greater than t Table 2.036. These results indicate that the application of Aqidah Akhlak learning management affects the learning motivation of class XI MIPA 1 MAN 2 Mojokerto.